Assessment of attitude towards innovative approaches related to nursing care in intensive care units among staff nurses of P.B.M. Hospital, Bikaner - Jangir, Ghanshyam; Yadav, Ashok (International Journal of Medical Research and Review, 2018)
Back ground: Innovation is process of developing new approaches, technologies and ways of working. It can apply to tools and technologies and processes, or the way anorganization or an individual behaves works or acts. Nursing care is changing in the face of technology, and innovation is the most important tool for improving the quality of care of community. Creativity and innovation are needed to continue the expression of genuine care and concern, not only through human contact, but also through the use of technology.Technology and its increased use in the healthcare field is constantly evolving and changing. The attitudes of the staff nurses can impact the successful use of that technology and thereby improve not only competency, but also job satisfaction, quality of nursing care. Objectives: 1. To assess the attitude towards innovative approaches related to nursing care in Intensive Care Unit (ICUs) among the staff nurses working in PBM hospital. 2. To associate the attitude towards innovative approaches among staff nurseswith selected background variable.3. To conduct the seminar on innovative approaches related to nursing care inICUs. Materials and Methods: Using non experimental study with descriptive design data were collected from 100 staff nurses working in ICUs. Likert type scale was used to collect data on attitude and structured questionnaire for back ground variable. Analysis of data was done using descriptive and inferential statistics. Results: Analysis of data showed statistically significant association between attitude towards innovative approaches and professional education and participation in continuing education among nurses. Study findings depicts positive attitude of nurses towards innovation in nursing care, whereas nurses working in ICUs have limited access to innovative and evidence based information. Conclusion: The study concluded that the attitude of staff nurses towards innovation in nursing care need to be enhanced by conducting educational training program and seminar on innovation in nursing care. There must be adequate access to information on innovative and evidenced based practice in nursing care.